THE POLLS: ATTITUDES TOWARD ORGANIZED LABOR. - Erskine, Hazel Gaudet (Public Opinion Quarterly)
The article reports that pollsters have explored public attitudes toward labor ever since the early days of sampling techniques. Many of the recent questions summarized in the article can be traced back in fairly comparable form to the 1930's. The periodical "Public Opinion Quarterly," is indebted to researcher George Gallup, the American Institute of Public Opinion, to the Gallup-affiliated Canadian Institute of Public Opinion and to researcher Limo Roper for some questions from the time when he published the Fortune Survey. In addition to some general attitudes toward union labor going back to 1936, topics include opinions on the closed shop and right to work laws, featherbedding, labor legislation in general, labor's political leanings, the minimum wage, the work week, and union finances. Technical questions about the information presented below should be directed to the original investigators, not to the journal. Dates shown are the times of release, not necessarily the dates the interviewing was done.